2023
DOI: 10.1037/sgd0000499
|View full text |Cite
|
Sign up to set email alerts
|

LGBQ activism and positive psychological functioning: The roles of meaning, community connection, and coping.

Abstract: In this study, we examined the relations between participation in lesbian, gay, bisexual, and queer (LGBQ) activism and posttraumatic growth and positive affect among 516 sexual minority persons. We also examined meaning in life, community connection, and problem-solving coping as potential explanatory variables in these links. We found that more participation in LGBQ activism was related to greater posttraumatic growth and more positive affect at the bivariate level. We also found that participation in LGBQ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 84 publications
2
12
0
Order By: Relevance
“…Within this sample, participants expressed that engaging in activism provided strength and resilience through the use of LGBTQ values to support others and in defying normative values within the United States. These findings are in line with recent research showing that posttraumatic growth among LGBQ communities tends to be facilitated through activism, relating to increased community connection, meaning in life, and problem-solving based coping (Szymanski et al, 2021). Examining the experience underlying the provision of community support by transgender and nonbinary peer supporters during the COVID-19 pandemic may uncover additional layers to vicarious trauma and posttraumatic growth.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Within this sample, participants expressed that engaging in activism provided strength and resilience through the use of LGBTQ values to support others and in defying normative values within the United States. These findings are in line with recent research showing that posttraumatic growth among LGBQ communities tends to be facilitated through activism, relating to increased community connection, meaning in life, and problem-solving based coping (Szymanski et al, 2021). Examining the experience underlying the provision of community support by transgender and nonbinary peer supporters during the COVID-19 pandemic may uncover additional layers to vicarious trauma and posttraumatic growth.…”
supporting
confidence: 91%
“…Current research on the effects of COVID-19 on LGBTQ populations in the United States provide ample consideration for the role of community support in mitigating trauma and psychological distress (Abreu et al, 2021; Szymanski et al, 2021). In a recent study, researchers found that five community and cultural values allowed community members to navigate the pandemic: activism; authenticity, pride, and visibility; collective intergenerational resilience; prioritizing mental health; and utilizing intersectionality in centering those most marginalized (Abreu et al, 2021).…”
mentioning
confidence: 99%
“…On one hand, activist purpose may be expected to yield some positive outcomes similar to other forms of purpose, such as greater health behaviors (see e.g., Kim et al., 2013), because individuals realize that to maintain their effort toward social activism, they must maintain better health and vitality. In addition, previous research has shown that engagement with activism was associated with greater posttraumatic growth, and that this relationship was mediated by a greater feeling of meaning in life (Szymanski et al., 2021). In a similar way, individuals who are able to find purpose in life through activism may experience better coping and psychological well‐being.…”
Section: Future Directionsmentioning
confidence: 94%
“…Studies that examine the political behavior of college students have found that African Americans who experience racism and discrimination experience lower levels of depression and anxiety when they outwardly support social justice groups, such as BLM [23,24]. Taking action, such as delivering a speech or participating in a protest, increases feelings of optimism and empowerment, and increases social solidarity and identification with one's racial and social class background, which have been shown in prior research to alleviate psychological distress [25][26][27]. Therefore, social activism may serve as a potent adaptive coping strategy for African Americans exposed to police-involved injuries and killings.…”
Section: Introductionmentioning
confidence: 90%